Implementation of virtual multicultural community conferences for school-based young generation in Yogyakarta - Suharno Suharno (Jurnal Civics: Media Kajian Kewarganegaraan)
This study examines virtual multicultural community encounters within Yogyakarta-based schools, focusing on their effects on the younger generation's comprehension of multiculturalism. Conducted in several schools, including SMAN 1 Wates and SMKN 2 Yogyakarta, using descriptive qualitative methods and purposive selection of Pancasila and Citizenship Education teachers, it gathered data through various means like interviews and focus group discussions. The research identified a significant impact of online encounters on participants' knowledge, awareness, understanding, and behavior towards multicultural communities, facilitated by virtual meetings aimed at fostering understanding and consensus. Crucial to this implementation was the influence of the majority-minority dynamic, with the predominance of Islam and Javanese culture being notable. The study underscores the value of these virtual encounters in promoting collaborative activities among diverse identities, highlighting a four-layered impact model. The research aims to both describe the practical implementation of these encounters and evaluate their substantive effects on young minds regarding multicultural understanding, suggesting a path forward for similar educational initiatives.